2022
DOI: 10.3390/brainsci12060793
|View full text |Cite
|
Sign up to set email alerts
|

Binge-like Prenatal Ethanol Exposure Causes Impaired Cellular Differentiation in the Embryonic Forebrain and Synaptic and Behavioral Defects in Adult Mice

Abstract: An embryo’s in-utero exposure to ethanol due to a mother’s alcohol drinking results in a range of deficits in the child that are collectively termed fetal alcohol spectrum disorders (FASDs). Prenatal ethanol exposure is one of the leading causes of preventable intellectual disability. Its neurobehavioral underpinnings warrant systematic research. We investigated the immediate effects on embryos of acute prenatal ethanol exposure during gestational days (GDs) and the influence of such exposure on persistent neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 167 publications
0
4
0
Order By: Relevance
“…In a recent study from our laboratory [4], we demonstrated in early postnatal rats that prenatal exposure to alcohol, at a relatively low concentration and for only 5 days, produces a number of drug-induced behaviors in the offspring, consistent with those described in clinical studies of children [26,[55][56][57][58][59]. These early behaviors stimulated by alcohol exposure include an increase in locomotor activity, anxiety, exploration, and alcohol-seeking behavior, and they are followed by a later increase in voluntary alcohol consumption during adolescence, consistent with other reports showing these behaviors to persist into adulthood [46,60,61]. This increase in alcohol consumption at a young age, induced by alcohol administered during pregnancy at a low concentration that increases blood alcohol to levels < 150 mg/dL, suggests that the required preference for alcohol is a conditioned response that is established prenatally [62,63].…”
Section: Behavioral Disturbances Observed In Rodent Studiessupporting
confidence: 86%
“…In a recent study from our laboratory [4], we demonstrated in early postnatal rats that prenatal exposure to alcohol, at a relatively low concentration and for only 5 days, produces a number of drug-induced behaviors in the offspring, consistent with those described in clinical studies of children [26,[55][56][57][58][59]. These early behaviors stimulated by alcohol exposure include an increase in locomotor activity, anxiety, exploration, and alcohol-seeking behavior, and they are followed by a later increase in voluntary alcohol consumption during adolescence, consistent with other reports showing these behaviors to persist into adulthood [46,60,61]. This increase in alcohol consumption at a young age, induced by alcohol administered during pregnancy at a low concentration that increases blood alcohol to levels < 150 mg/dL, suggests that the required preference for alcohol is a conditioned response that is established prenatally [62,63].…”
Section: Behavioral Disturbances Observed In Rodent Studiessupporting
confidence: 86%
“…Interestingly, multiple genes that were significant for a strain × treatment interaction and showed a fold-change greater than 1.5 are involved in apoptosis-related pathways and have previously been linked to FASD including Bcl2l11 [ 62 ], Dusp1 [ 62 ], Egr3 [ 62 , 63 ], Fgf1 [ 64 , 65 ] Jun [ 62 , 66 ], Pik3r1 [ 62 ] Tgfb3 [ 62 , 67 ], and Txnip [ 62 , 66 ]. Moreover, many genes that showed differential ethanol-induced gene expression changes have been previously linked to gene expression changes in the brain of B6 mice using the same ethanol exposure paradigm as used in the current study [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both Irs2 and Fgf1 were up regulated in LCD males after ethanol exposure. Interestingly, studies that previously reported ethanol-induced alterations in Irs2 and Fgf1 reported down-regulation after ethanol exposure [ 64 , 129 , 130 ]. However, sex-specific increases of Irs2 in males after exposure to prenatal ethanol have also been reported [ 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that FAE induced spatial memory impairments in both male and female offspring. Previous studies in animal models of FAE have demonstrated a deficit in hippocampal‐dependent learning and memory that persist in the adulthood in a mouse (Brady et al, 2012; Subbanna & Basavarajappa, 2022) and a rat (Sanchez et al, 2019) models of FAE. Also, children with FAE often show verbal learning and spatial memory deficits and abnormal hippocampal functions (Dodge et al, 2019; Neil et al, 2020; Willoughby et al, 2008).…”
Section: Discussionmentioning
confidence: 98%